Does the Cognitive Measure Cog-4 Show Improvement among Patients Treated with Thrombolysis after Acute Stroke?. Issue 8 (December 2013) - Hajjar, Karim; Fulton, Rachael L.; Diener, Hans-Christoph; Lees, Kennedy R.; ,; Alexandrov, A; Bath, PMW; Bluhmki, E; Claesson, L; Curram, J; Davis, SM; Donnan, G; et al.
Background: Although the established measure of disability post stroke, the modified Rankin Scale emphasizes motor function and may underestimate the importance of cognitive impairment in more disabled patients. A subset of four items from the National Institutes of Health Stroke Scale has been proposed to assess cognitive function after stroke (Cog-4), and to correlate with modified Rankin Scale. Items correspond to orientation, executive function, language, and inattention. We investigated responsiveness of Cog-4 to treatment with thrombolysis and whether it offers information that supplements modified Rankin Scale. Methods: We included 6268 patients from the Virtual International Stroke Trials Archive: 2734 received intravenous thrombolysis and 3534 were treated conservatively. We compared day 90 outcomes between treated and untreated groups, by modified Rankin Scale (illustrative) and by Cog-4 (primary measure) adjusting for age, baseline National Institutes of Health stroke scale, hemispheric lateralisation as well as baseline Cog-4 and baseline National Institutes of Health Stroke Scale excluding baseline Cog-4 separately. Analysis of Cog-4 was repeated within strata of 90 day modified Rankin Scale. Statistical analyses included proportional odds logistic regression and Cochran–Mantel–Haenszel test. Results: Modified Rankin Scale showed a difference between treatment groups of expected magnitude (odds ratio 1·56; 95% confidence interval 1·43–1·72; P < 0·001). After adjustment for imbalance in baseline prognostic factors, the distribution of Cog-4 scores at 90 days was better in thrombolysed patients compared with nonthrombolysed patients (odds ratio 1·31; 95% confidence interval 1·18–1·47; P = 0·006). However, Cog-4 analysis stratified by 90-day modified Rankin Scale was neutral between treatment groups (OR 1·01; 95% CI 0·90–1·14), and Cog-4 was not responsive to treatment group even within modified Rankin Scale categories 4 and 5 despite substantial cognitive deficits in these patients. Conclusion: Although Cog-4 may be responsive to treatment effects, it does not provide additional information beyond modified Rankin Scale assessment.